Representasi Komunikasi Keluarga dalam Film “Sejuta Sayang Untuknya” - Muhammad Pradika Ikbal Firdaus; Dedeh Fardiah (UNISBA Press, 2023)
Abstract. Representation of a film “My Million For Her” is the focus of this research. The film focuses on this family conflict as an entity in understanding the meaning of real life. The semiotic analysis of Roland Barthes on Herwin Novianto's film